Clinical Epidemiology of Pediatric COVID-19 Delta Variant Cases From North Sumatra, Indonesia - Kusumawati, R. Lia; Lubis, Inke Nadia Diniyanti; Kumaheri, Meutia Ayuputeri; Pradipta, Ariel; Faksri, Kiatichai; Mutiara, Mutiara; Shankar, Anuraj H.; Tania, Tryna (Frontiers in Pediatrics, 2022)
The Delta variant of SARS-CoV-2 has dominated the COVID-19 pandemic in 2021. Here we report the Delta variant among paediatric cases in North Sumatra, Indonesia, from June-July 2021. Whole-genome sequences (WGS) from 18 new COVID-19 paediatric patients showed that 6 were B.1.459 and 6 were B.1.466.2, known variants in Indonesia in Clade 20A. Six were the Delta variant B.1.617.2 of Clade 21A, with 5 on one branch, and one on a distant branch consistent with that patient’s geographic separation, suggesting at least two introductions to the region. Variants tended to be spatially clustered, and four children with Delta variant had an adult infected household member, all of whom had lower real-time polymerase chain reaction (RT-PCR) cycle threshold (Ct) values compared to the child. No temporal trends were observed for Ct. These data support a paradigm shift with children being highly susceptible to the Delta variant and a priority for vaccination.